Будівничий рециклінг гальваношламів як суспільно-господарська потреба промисловості майбутнього - Гуща, А. А. (ХНУРЕ, 2020)
Galvanic production is one of the dangerous sources environmental pollution. Therefore, the problem of processing and disposal of liquid and solid waste (sediments) formed in the process of neutralization of industrial effluents of electroplating industries has recently become of great importance.
Keywords: будівничий рециклінг гальваношламів; мінеральна сировина; пластифікуючий ефект